2022
DOI: 10.1002/jcsm.13047
|View full text |Cite
|
Sign up to set email alerts
|

Associations between frailty trajectories and cardiovascular, renal, and mortality outcomes in chronic kidney disease

Abstract: Background Frailty is characterized by the loss of biological reserves and vulnerability to adverse outcomes. In individuals with chronic kidney disease (CKD), numerous pathophysiological factors may be responsible for frailty development including inflammation, physical inactivity, reduced energy intake, and metabolic acidosis. Given that both CKD and frailty incur a significant healthcare burden, it is important to understand the relationship of CKD and frailty in real-world routine clinical practice, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“… 8 , 9 ) Unfortunately, frailty is common, affecting an estimated 11% of community-dwelling adults aged ≥65 years. 11 ) The prevalence of frailty is especially high in the oldest older adults (≥80 years), 12 ) those residing in low- and middle-income countries, 13 ) residents of long-term care facilities, 14 ) and populations with chronic diseases such as chronic obstructive pulmonary disease, 15 ) chronic kidney disease, 16 ) cancer, 17 ) and cardiovascular disease. 18 ) The likelihood of developing frailty is affected by inequalities in socioeconomic position.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 ) Unfortunately, frailty is common, affecting an estimated 11% of community-dwelling adults aged ≥65 years. 11 ) The prevalence of frailty is especially high in the oldest older adults (≥80 years), 12 ) those residing in low- and middle-income countries, 13 ) residents of long-term care facilities, 14 ) and populations with chronic diseases such as chronic obstructive pulmonary disease, 15 ) chronic kidney disease, 16 ) cancer, 17 ) and cardiovascular disease. 18 ) The likelihood of developing frailty is affected by inequalities in socioeconomic position.…”
Section: Introductionmentioning
confidence: 99%
“…PEF monitoring, as an easily accessible lung function index, has been found to be non-inferior to spirometry for screening purposes of lung dysfunction 37. Additionally, PEF has been described as a component of the diagnosis of respiratory sarcopenia, which is associated with worsened renal function and a high risk of ESRD 38–40…”
Section: Discussionmentioning
confidence: 99%
“…Illnesses: Participants reported whether they had been diagnosed with the following conditions: hypertension (subjects were diagnosed as hypertension when the systolic blood pressure was ≥140 mmHg or the diastolic pressure was ≥90 mmHg or self-reported hypertension), dyslipidemia, diabetes, cancer (excluding mild skin cancer), lung disease, liver disease, heart disease, stroke, stomach disease, depression, memory-related disease and arthritis/rheumatism. For this analysis, to investigate the role of the index independent of CKD, we removed CKD (9). Participants with ≥5 diseases were de ned as having the disease.…”
Section: Assessment Of Frailtymentioning
confidence: 99%
“…For example, Roshanravan et.al found that the prevalence of frailty (14.0%) in CKD participants was twice that of the much older non-CKD reference population (P < 0.01) and the frailty phenotype was associated with an estimated 2.5 (95% CI, 1.4-4.4)-fold greater risk of death or dialysis therapy(8). Besides, a study involving 819 893 participants aged ≥ 40 years found that the majority of those with CKD (75.3%) were frail [vs. 45.4% in those without CKD (no-CKD)] and frailty was associated with increased rates of end-stage kidney disease (ESKD) and all-cause and cardiovascular-related mortality (9). However, whether frailty leads to an increased incidence of CKD remains an under-explored question.…”
Section: Introductionmentioning
confidence: 99%